Study the Effect of Electromagnetic Radiation towards Sustainable Healthy Buildings - Elkabany, Sara Nabeel (Journal of engineering sciences and information technology, 2023)
In this study, the electromagnetic waves were defined with an explanation of their physical properties and negative biological effects on humans, where the importance of research appears in defining the concept of sustainability, leading to the construction of guiding standards that help designers to reach for sustainable architecture for healthy buildings. Accordingly, the research hypothesizes that sustainable buildings are high-efficiency buildings that reduce negative impacts on the environment and human health, and are designed to be economical in resource consumption. In this study, the sources and negative effects of electromagnetic fields on human health were identified as a problem and some suggestions were presented to solve them and prevent negative electromagnetic radiations from affecting human health by setting standards for protecting buildings from the negative effects of electromagnetic radiation. The main objective of this study is to reach a set of results that enable the achievement of eco-friendly buildings that take into account human needs and health.